Comparison between efficacy of spinal mobilization with leg movement versus McKenzie technique in patients with lumbar disc herniation - Mohammad N. Selim; Maha M. Mokhtar; Mahmoud H. Mohamed; Asmaa A. Abonour; Sahar M. Abdelmutilibe; Mohamed M. M. Essa (Universidad de Murcia, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.